2020
DOI: 10.3390/plants9020164
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rhododendron arboreum Leaf Extract on the Antioxidant Defense System against Chromium (VI) Stress in Vigna radiata Plants

Abstract: In the current investigation, we studied role of Rhododendron leaf extract in Vigna radiata grown under chromium metal stress. We observed that seed treatment with Rhododendron leaf extract resulted in the recuperation of seedling growth under chromium toxicity. Seed treatment with Rhododendron leaf extract significantly improved the contents of anthocyanin and xanthophyll pigments under stress. The antioxidative defense system triggered after Rhododendron extract treatment, resulting in the increased actions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 69 publications
2
7
0
Order By: Relevance
“…Aestivum [ 18 ]. Similar results have been observed in various plants subjected to Cr toxicity [ 11 , 20 , 67 , 68 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Aestivum [ 18 ]. Similar results have been observed in various plants subjected to Cr toxicity [ 11 , 20 , 67 , 68 ].…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies have shown that APX activity decreased with increased metal toxicity in Brassica juncea (L.) [65], B. napus [66], and T. Aestivum [18]. Similar results have been observed in various plants subjected to Cr toxicity [11,20,67,68].…”
Section: Plos Onesupporting
confidence: 78%
“…Reports also showed that some plants in the Rhododendron genus presented anti-inflammatory and antioxidant activities, such as R. tomentosum ssp . subarcticum ( Black et al, 2011a , b ) , R. arboreum ( Gautam et al, 2020 ) and R. ponticum ( Erdemoglu et al, 2008 ). In this paper, the anti-inflammatory activity of R. przewalskii extracts in vitro was evaluated for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…14 Oxidative stress markers such as SOD, CAT and MDA were measured in tissue and also measured the concentration of inflammatory markers like interleukin-6 (IL-6) interleukin-1beta (IL-1β) and tumor necrosis factor-alpha (TNF-α) as well as VEGF, a specific sepsis marker. The test drug given group were significantly restored all the markers of liver and renal functions, antioxidant markers and also normalized plasma pro-inflammatory cytokines, thus preventing the multi-organ and tissue damage in LPS induced rats [15][16] .…”
Section: Traditional Usesmentioning
confidence: 85%